Development of a Literacy House to Increase Interest in Reading in Children - Syaeful Bakhri; Anisa Suhada Putri (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
Interest is a combination of desire and will that can develop if there is motivation. If interest and motivation are absent, habits generally don't grow and don't develop. The habit of reading must be applied from an early age, in order to overcome the problem of a lack of interest in reading in children. The creation of a "Reading Corner" is provided in order to provide a solution to the low ability of children to read and write at school age. There are several things that cause low interest in reading, one of which is how parents do not encourage children to prioritize buying books over toys, hearing aids. The role of mentoring is related to efforts to foster children's learning motivation from an early age, namely providing teaching, mentoring, and setting a good example for children. Therefore, this research was conducted with the aim of providing assistance in the process of fostering motivation to read in children through collaboration with local residents to build interest in reading in children from an early age.